Peranan iklim organisasi sebagai pemboleh ubah penyederhanaan ke atas hubungan budaya organisasi dan amalan kerja berprestasi tinggi - Mohd Isa, Mohd Faizal; Zainal, Arifin; Wan Mohd Noor, Wan Shakizah; Daud, Zulkiflee; Omar, Fatimah (2012)
Today;s world business competition become more open and challenging, This situation demands the organizations more focused to evaluate their role of internal factor such as value and work environment become more quality and competitive advantage.This study was undertaken to explore the influence of organizational climate in the relationship between organizational culture and high performance work system.A cross-sectional survey was performed to identify the current scenario of internal perception among 187 employees in Malaysian broadcasting industry. Result from hierarchy multiple regression analysis showed that there were significant interaction between organizational culture and organizational climate with high performance work system.The findings of this study confirm that the organizational climate acted as a moderator for high performance work system in the organization.Results suggest that greater use of high performance work systems is associated with positive organizational culture and climates.